2018
DOI: 10.1111/avj.12720
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal non‐invasive soak under general anaesthetic to treat fungal rhinitis in an Australian Quarter Horse gelding at pasture

Abstract: Mycotic rhinitis is an unusual disease that can be difficult to treat successfully. This report describes a technique for topical sinonasal bathing under general anaesthetic that was well tolerated, easy to perform and resulted in a successful clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
4
0
4
Order By: Relevance
“…Os sinais clínicos mais observados são dispneia, sons respiratórios anormais, diminuição da passagem de ar pelas vias aéreas, secreção nasal uni ou bilateral podendo ter odor fétido e epistaxe (Lean & Ahern, 2018). Em um estudo com 10 cavalos com rinite micótica, o único sinal clínico consistente foi a presença de secreção unilateral fétida (McGorum et al, 1992).…”
Section: Discussionunclassified
“…Os sinais clínicos mais observados são dispneia, sons respiratórios anormais, diminuição da passagem de ar pelas vias aéreas, secreção nasal uni ou bilateral podendo ter odor fétido e epistaxe (Lean & Ahern, 2018). Em um estudo com 10 cavalos com rinite micótica, o único sinal clínico consistente foi a presença de secreção unilateral fétida (McGorum et al, 1992).…”
Section: Discussionunclassified
“…Topical application of the antifungal drug is commonly used because it results in higher therapeutic concentrations over the mycotic plaque and decreases the risk of toxicity. One of the authors has reported a successful technique using topical fluconazole sinonasal bathing under general anaesthetic for treatment of a chronic fungal rhinitis in a horse (Lean and Ahern 2018) ( Fig ). This technique has been used previously in small animals for treatment of canine nasal aspergillosis (Mathews et al .…”
Section: Figurementioning
confidence: 99%
“…A rare case report describes a Quarter horse gelding that presented with chronic mucopurulent nasal discharge and dyspnoeas, that persisted after 9 months of medical treatment …”
Section: Equinementioning
confidence: 99%